Peer‐to‐Peer Education in First‐Year Dentistry: A Reciprocal Benefit for Oral Health Knowledge and Early Dental Education - Ahmet Mert Nalbantoğlu; Beyza Ballı Akgöl; R. Gözde Kırzıoğlu Ercan; Deniz Yanık Nalbantoglu; Şule Bulut; Nil Altay (European Journal of Dental Education, 2026)
ABSTRACT Introduction The study aims to evaluate the effect of peer‐to‐peer oral health education performed by dental students using three different teaching materials. Materials and Methods Seventy‐four first year students at the university, faculty of dentistry, who took part as peer educators, were divided into three groups according to the teaching material; Group I: teaching with 2D‐material (brochure), Group II: teaching with 2D‐dynamic material (video), and Group III: teaching with 3D‐material (dental model) and gave oral and dental health education to students at the university. These training materials included information such as the correct method of tooth brushing, the duration and frequency of tooth brushing, and dental floss. Before and 7–10 days after the education, an oral health scale consisting of 10 questions was applied to the participants to measure their level of oral health knowledge. Results A total of 1077 students at the university participated, of which 380 were trained by Group I, 336 by Group II, and 361 by Group III. The correct answers increased significantly following the education for most questionnaire items across three educational methods ( p < 0.05). Group III was statistically significantly more effective than the other teaching materials. No statistically significant difference was found between Group I and Group II ( p > 0.05). Conclusion Peer‐to‐peer education performed by first‐year dental students enhanced the oral health knowledge of the university students. The dental model was more effective than brochures and videos in increasing oral health knowledge.